Computer Processing of Oriental Languages. Beyond the Orient: The Research Challenges Ahead 21st International Conference, ICCPOL 2006, Singapore, December 17-19, 2006, Proceedings - Matsumoto, Yuji; Sproat, Richard; Wong, Kam-Fai; Zhang, Min (Lecture Notes in Artificial Intelligence, 2006)
This book constitutes the thoroughly refereed proceedings of the 21st International Conference on Computer Processing of Oriental Languages, ICCPOL 2006, held in Singapore in December 2006, colocated with ISCSLP 2006, the 5th International Symposium on Chinese Spoken Language Processing. The 36 revised full papers and 20 revised short papers presented were carefully reviewed and selected from 169 submissions. The papers are organized in topical sections on information retrieval, document classification, questions and answers, summarization, machine translation, word segmentation, chunking, abbreviation expansion, writing-system issues, parsing, semantics, and lexical resources.